2020
DOI: 10.3390/smartcities4010003
|View full text |Cite
|
Sign up to set email alerts
|

Smart City Strategies—Technology Push or Culture Pull? A Case Study Exploration of Gimpo and Namyangju, South Korea

Abstract: This study aims to address strategies, models, and the motivation behind smart cities by analyzing two smart city project cases in medium-sized cities, i.e., Gimpo and Namyangju in South Korea. The case of Smartopia Gimpo represents a top-down, infrastructure-focused smart city innovation that invested in building state-of-the-art big data infrastructure for crime prevention, traffic alleviation, environmental preservation, and disaster management. On the other hand, Namyangju 4.0 represents a strategy focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 33 publications
0
31
0
4
Order By: Relevance
“…= 0.000) and air pollution management (rho = 0.602 **, sig. = 0.001) is significantly positive [48]. Previous evaluations of collaborative pieces of evidence in the following cases have indicated that decisions to promote government regulations concerning air pollution control require a concise problem, a clearly defined problem-solving strategy, and leadership to support at least some important cooperative groups.…”
Section: Role Of Innovative Leadershipmentioning
confidence: 82%
“…= 0.000) and air pollution management (rho = 0.602 **, sig. = 0.001) is significantly positive [48]. Previous evaluations of collaborative pieces of evidence in the following cases have indicated that decisions to promote government regulations concerning air pollution control require a concise problem, a clearly defined problem-solving strategy, and leadership to support at least some important cooperative groups.…”
Section: Role Of Innovative Leadershipmentioning
confidence: 82%
“…However, in large-scale IoT networks, to relieve the load on the IoT platform, a portion of storage and computation tasks are allocated to the edge devices [ 16 ]. In Gimpo-si, an IoT-based sensor service was built for crime prevention [ 17 ]. The edge computing device, such as a mobile device, cannot afford to store the metadata of all the sensors in a medium-sized city.…”
Section: Related Workmentioning
confidence: 99%
“…В городе тестируются и применяются различные технологии «умного дома» и «умного города», тем самым привлекая внимание международных инвесторов к реализации последующих проектов в этом направлении 19 . Параллельно ведется разработка еще двух проектов «умных городов» -Кимпхо (Smartopia Gimpo) и Намянджу (NamYangJu 4.0) (Myeong et al, 2021). Первый проект сосредоточился на обеспечении безопасности граждан, предупреждении преступности и оповещении о стихийных бедствиях с помощью таких технологий, как Интернет вещей и большие данные.…”
Section: рис 2 стратегические инициативы (программы) по развитию цифровой экономики в южной корее / Fig 2 Strategic Initiatives (Programsunclassified